Review of Scydmaenus (Geoscydmaenus) of Madagascar (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Two species of Scydmaenus (Geoscydmaenus) are known to occur in Madagascar, but original descriptions do not allow for unambiguous identification. Based on the type specimens and a recently collected additional material, Sc. isaloensis Franz and Sc. madagassicus Franz are redescribed. Several differences between these species listed by Franz had been misinterpreted; consequently species diagnoses are emended. Morphological structures of Geoscydmaenus are illustrated and discussed, and it is concluded that in future this taxon may be elevated to genus rank. However, as morphological structures of most subgenera of Scydmaenus remain exceptionally poorly studied and knowledge of character variability is scarce, it is too early to reclassify this large genus.